2008
DOI: 10.1111/j.1744-6155.2008.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Differences in Weight, Length, and Weight for Length of Mexican American Children in the WIC Program

Abstract: PURPOSE Examine factors common in the environments of children who obtain services from a WIC program to determine if differences in ecological/environmental factors can be found in the children who differ in weight, length, and weight for length. DESIGN AND METHODS Cross-sectional study of 300 children, 100 each who were stunted, normal weight for length, or overweight. Instruments used were NCATS, ARSMA II, 24-hr diet recall, and Baecke Activity Questionnaire. RESULTS Significant differences were present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 61 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…Emphasis on neighborhood social environment is compatible with MA values, with implications for nursing interventions. Family influence in our study is consistent with results of a study of younger (12–24 months) MA children's weights, in which overweight children had high carbohydrate intake from family eating environments (Reifsnider & Ritsema, 2008). Similar to youths' preferences in our study, in a study of female Hispanic/Latino adolescent seeking help, adolescents sought help more from informal than formal sources (Rew, Resnick, & Blum, 1997).…”
Section: Discussionsupporting
confidence: 91%
“…Emphasis on neighborhood social environment is compatible with MA values, with implications for nursing interventions. Family influence in our study is consistent with results of a study of younger (12–24 months) MA children's weights, in which overweight children had high carbohydrate intake from family eating environments (Reifsnider & Ritsema, 2008). Similar to youths' preferences in our study, in a study of female Hispanic/Latino adolescent seeking help, adolescents sought help more from informal than formal sources (Rew, Resnick, & Blum, 1997).…”
Section: Discussionsupporting
confidence: 91%
“…Dietary intake differs significantly in overweight versus normal weight Hispanic infants. In a comparison study of Mexican American children, Reifsnider and Ritsema () found significant differences in the dietary intake of overweight infants. The overweight group had significantly higher daily intakes of Mexican rice and Kool‐Aid and shorter duration of breastfeeding compared to a group of normal growing infants.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have documented that formula fed infants have higher intakes of energy [21] and protein [23] than breastfed infants. Similarly, Reifsnider and colleagues [24] reported significant differences in the A C C E P T E D M A N U S C R I P T health disparities like obesity. The primary aim of this study was to explore differences in modifiable feeding factors (maternal feeding practices, feeding pattern, and dietary intake) by overweight status (> 85% weight-for-length) in the first year of life.…”
Section: Modifiable Feeding Factors By Overweight Statusmentioning
confidence: 95%